Pengaruh Tandan Kosong Kelapa Sawit pada Media Buatan terhadap pH, Fe, dan Mn untuk Pengelolaan Air Asam Tambang - Nurul Syamsiah; Bambang Joko Priatmadi; Abdul Hadi (Acta Solum, 2022)
Indonesia is a coal producing country and coal mining activities are carried out using the open pit method. The activity resulted in the acid mine drainage (AMD). AMD has low pH and contains high concentrations of heavy metals ions such as aluminum (Al), iron (Fe) dan manganese (Mn). One of the interesting technologies in the AMD treatment is passive treatment using constructed wetland. The system can increase pH and reduce level of dissolved metals. Oil palm empty fruit bunches (OPEFB) are potential to improve soil pH, because they have a high nutrient content such as N, P, and K. This study aims to determine the effect of OPEFB as amendment material on artificial wetland media on pH, Fe, Mn in AMD management. The method used was a single Randomized Complete Design with the treatment of OPEFB of 0, 100, 200, 300, and 500 g 5.5 kg-1 soil then replicated four times. The results showed that oil palm empty fruit bunches high significant increase in pH, Fe, Mn and 100 g 5.5 kg-1 soil doses effectively used for the AAT management by passive treatment as fulfilled the mining liquid waste quality standards according to the Ministerial Decree State of the Environment Number 113 of 2003 and South Kalimantan Province Governor Regulation Number 04 of 2007.